Dynamics of non-structural carbohydrates in three Mediterranean woody species following long-term experimental drought - Rosas, Teresa; Galiano, Lucía; Ogaya, Romà; Peñuelas, Josep; Martínez-Vilalta, Jordi (Frontiers in Plant Science, 2013)
Stored non-structural carbohydrates (NSC) have been proposed as a key determinant of drought resistance in plants. However, the evidence for this role is controversial, as it comes mostly from observational, short-term studies. Here, we take advantage of a long-term experimental throughfall reduction to elucidate the response of NSC to increased drought 14 years after the beginning of the treatment in three Mediterranean woody species (Quercus ilex L., Arbutus unedo L. and Phillyrea latifolia L.). In addition, we selected 20 Q. ilex individuals outside the experimental plots to directly assess the relationship between defoliation and NSC at the individual level. We measured the seasonal course of NSC concentrations in leaves, branches and lignotuber in late winter, late spring, summer and autumn 2012. Total concentrations of NSC were highest in the lignotuber for all species. In the long-term drought experiment we found significant depletion in concentrations of total NSC in treatment plots only in the lignotuber of A. unedo. At the same time, A. unedo was the only species showing a significant reduction in BAI under the drought treatment during the 14 years of the experiment. By contrast, Q. ilex just reduced stem growth only during the first 4 years of treatment and P. latifolia remained unaffected over the whole study period. However, we found a clear association between the concentrations of NSC and defoliation in Q. ilex individuals sampled outside the experimental plots, with lower total concentrations of NSC and lower proportion of starch in defoliated individuals. Taken together, our results suggest that stabilizing processes, probably at the stand level, may have been operating in the long-term to mitigate any impact of drought on NSC levels, and highlight the necessity to incorporate long-term experimental studies of plant responses to drought.